Counselling Psychology in the UK: a critical-humanistic perspective. (2nd January 2016) - House, Richard; Feltham, Colin
Abstract : In this broad analysis of the history, current state and future prospects of Counselling Psychology as a distinct branch of the Psychology discipline, we first describe how Counselling Psychology emerged historically, and we then review the ways in which Counselling Psychology offers something quite distinct from the mainstream discipline, and which could even begin to resemble a kind of genuinely ' critical psychology'. We offer a nine-point 'prospectus' setting out the value of Counselling Psychology, focusing in particular on its specifically humanistic contributions within Psychology; we also consider its limitations. We urge that non-defensive and engaged attention be given to serious critiques of the psychological therapies, and we advocate ongoing, genuinely critical engagement with such challenges, such that an authentically critical-radical Counselling Psychology might become a genuine possibility.